The crystal structures of [Met5]enkephalin and a third form of [Leu5]enkephalin: observations of a novel pleated beta-sheet. - Griffin, J F (1986)
The structures of [Met5]enkephalin (Tyr-Gly-Gly-Phe-Met) and [Leu5]enkephalin (Tyr-Gly-Gly-Phe-Leu) have been determined from single crystal x-ray diffraction data and refined to residuals of 0.100 and 0.092, respectively. The [Met5]enkephalin structure consists of dimers forming antiparallel beta-sheets extending in the monoclinic ac plane with 10.6 water molecules per dimer. The two molecules, related by pseudo two-fold axes, have similar backbone conformations and similar tyrosine and phenylalanine side-chain conformations. Both methionine residues are disordered and the disorder is different in the two independent molecules. Additional hydrogen bonds connect adjacent dimers to form infinite sheets normal to the b axis. The water molecules are found mainly in the interstices between the sheets. [Leu5]Enkephalin crystallizes as a monohydrate that is isomorphous with the [Met5]enkephalin structure with respect to the beta-sheet but different with respect to the tyrosine and phenylalanine side-chain conformations and water content. The peptide chains in both structures are fully extended and more nearly planar than pleated. The planes of the peptide chains in the dimers form an angle of 143.3 degrees with one another in [Met5]enkephalin and 156.0 degrees in [Leu5]enkephalin. This produces a zigzag pattern or pleat in the beta-sheets perpendicular to the direction of the peptide chains and, therefore, perpendicular to the normal beta-sheet pleat. The average repeat distance between Ni and Ni+2 in the peptide chains of both structures is 7.10 A, versus an ideal value of 6.68 A.